Implementation of Work Discipline on the Performance of KJ Pharmacy Employees - Deviani, Elmira; Isyanto, Puji; Yani, Dini (Journal Integration of Social Studies and Business Development, 2023)
Work discipline is a condition created and formed through a series of behaviors that show the values of obedience, obedience, tranquility, order, and order. Work discipline is a person's awareness and willingness to obey all company regulations and applicable social norms, where an employee always comes and goes home on time so that he does all work well using descriptive methods with qualitative data by collecting observation data directly at the company. Work discipline is applied by providing regulations regarding attendance time, applying operational work standards, and compliance with company regulations. The company also follows up on the attitudes and behaviors of its employees by sanctioning employees who do not apply the discipline that applies in the company; work discipline will also affect employee performance.